An analysis of the clinical and imaging features of mitochondrial encephalopathy, lactic acidosis, and stroke-like episodes (MELAS). (2nd January 2020) - Chen, Hao; Hu, Qian; Raza, Hafiz Khuram; Chansysouphanthong, Thitsavanh; Singh, Sandeep; Rai, Pabitra; Cui, Guiyun; Zhang, Zuohui; Ye, Xinchun; Xu, Chuanying; Liu, Yonghai; Jiang, Haiyang
Abstract: Objective: To investigate the clinical features and imaging characteristics of mitochondrial encephalopathy, lactic acidosis, and stroke-like episodes (MELAS). Methods: Seventeen patients with MELAS diagnosed in the Affiliated Hospital of Xuzhou Medical University from July 2014 to August 2018 were enrolled in this study and their clinical manifestations, imaging and histopathological features were retrospectively analysed. We also discussed and summarised the related literature. Results: All of the 12 patients had seizures; stroke-like episodes in 12 cases; audio-visual impairment in 12 cases; headache in six cases; dysplasia in four cases; mental retardation in three cases; ataxia in two cases. On cranial magnetic resonance (MR) scans, the most common manifestations were in temporal–occipital–parietal lobe, cortical or subcortical areas as well as frontal lobe, thalamus, and basal ganglia showing long or equal T1 signals, long T2 signals, and hyperintense or iso-intense diffusion-weighted imaging (DWI) signals accompanied by ventricular enlargement and brain atrophy. MR spectroscopy showed that lactic acid peaks could be found in lesion sites, normal brain tissues, and cerebrospinal fluid. Muscle biopsy and genetic testing are the gold standard for diagnosing MELAS, muscle biopsy revealed COX-negative muscle fibres and SDH-stained red ragged fibres (RRF) under the sarcolemma. Mutations of mtDNA A3243G locus were common on gene testing. Improvement of mitochondrial function was observed after symptomatic and supportive treatment. Conclusion: MELAS should be considered for patients with epileptic seizures, headache, stroke-like episodes, extraocular palsy, cognitive decline and other clinical manifestations with the lesion located in the temporal–occipital–parietal lobe regardless of the distribution of blood vessels, and further examinations including muscle biopsy and gene testing should be performed to confirm the diagnosis.